APLIKASI PUPUK ORGANIK CAIR LIMBAH SAYURAN PADA PERTUMBUHAN DAN PRODUKSI SAWI PAKCOY (Brasicca Rapa L.) DAN SAWI HIJAU (Brasicca Juncea L.) - Kleor, Fransesko Rudianto; Astutik, Astutik; Sutoyo, Sutoyo (Fakultas Pertanian, 2018)
This study aims to find out the interaction between the dose of liquid organic fertilizer given to the growth and production of mustard pakcoy and mustard greens. The study was conducted at the Green House Integrated Field Laboratory of Tribhuwana Tunggadewi University, Malang City for 3 months. The study used a Completely Randomized Design with 12 combinations of treatments and 3 replications consisting of two factors, namely: Factor I consisted of 2 varieties namely mustard pakcoy and mustard green and Factor II namely the dosage of Liquid Organic Fertilizer consisting of: 0 ml / L water / plant, 150 ml / L water / plant, 300 ml / L water / plant, 450 ml / L water / plant, 600 ml / L water / plant and 750 ml / L water / plant. Observation variables of plant height, number of leaves, leaf area, fresh weight per plant, fresh weight per ha. The results of the study concluded that there was no interaction between the mustard plant type and the POC dose of vegetable waste which is given. POC dosage of vegetable waste up to 750 ml / L of water does not affect the growth and yield of mustard plants. Growth and yield of mustard greens plants are higher than that of mustard pakcoy with a yield of mustard green plants 41.35 t.ha-1 and mustard pakcoy 33.83 t.ha-1 Â¬. Penelitian bertujuan untuk mengetahui interaksi antara dosis pupuk organik cair yang diberikan pada pertumbuhan dan produksi tanaman sawi pakcoy dan sawi hijau. Penelitian dilaksanakan di Green House Laboratorium Lapang Terpadu Universitas Tribhuwana Tunggadewi, Kota Malang selama 3 bulan. Penelitian menggunakan Rancangan Acak Lengkap dengan 12 kombinasi perlakuan dan 3 ulangan yang terdiri dari dua faktor yaitu : Faktor I terdiri dari 2 varietas yaitu Sawi Pakcoy dan Sawi Hijau dan Faktor II yaitu dosis Pupuk Organik Cair yang terdiri dari : 0 ml/L air/tanaman, 150 ml/L air/tanaman, 300 ml/L air/tanaman, 450 ml/L air/tanaman, 600 ml/L air/tanaman dan 750 ml/L air/tanaman. Variabel pengamatan tinggi tanaman, jumlah daun, luas daun, bobot segar per tanaman, bobot segar per ha. Hasil penelitian disimpulkan bahwa tidak ada interaksi antara jenis tanaman sawi dan dosis POC limbah sayuran yang diberikan. Dosis POC limbah sayuran sampai dengan 750 ml/L air tidak berpengaruh terhadap pertumbuhan dan hasil tanaman sawi. Pertumbuhan dan hasil tanaman sawi hijau lebih tinggi dibandingkan sawi pakcoy dengan hasil tanaman sawi hijau 41,35 t.ha-1 dan sawi pakcoy 33,83 t.ha-1Â¬.